Compositional dependence of photovoltaic properties of Cu2ZnSnSe4 thin film solar cell: Experiment and simulation. (1st January 2018) - He, Jun; Lu, Xiaoshuang; Li, Xinran; Dong, Yuchen; Yue, Fangyu; Chen, Ye; Sun, Lin; Yang, Pingxiong; Chu, Junhao
Highlights: The influence of Cu composition on the properties of CZTSe thin film. [CuZn  + ZnCu ] defect cluster and MoSe2 may result in large Voc deficit and high Rs, respectively. The conversion efficiency of Cu-poor CZTSe solar cell is 4.83%. Abstract: In this paper, we have investigated the influence of Cu composition on the properties of Cu2 ZnSnSe4 (CZTSe) thin film, and the device performances of CZTSe solar cells. CZTSe thin films were fabricated by selenization of sputtered stacked metallic precursors, and the conversion efficiency of Cu-poor CZTSe solar cell is 4.83%. The device simulation on CZTSe solar cell combined with experimental data indicates that the Cu-poor sample with lower ZnCu donor defect concentration exhibits relatively high efficiency. The large open circuit voltage ( Voc ) deficit and high series resistance ( Rs ) are responsible for the efficiency limitation of Cu-poor CZTSe solar cell. Large Voc deficit and high Rs are likely to originate from [CuZn  + ZnCu ] defect cluster and the formed MoSe2 between CZTSe and Mo films, respectively.